České a ukrajinské pranostiky jako kulturologický pramen - Trmačová, Ivana (2006)
History of national calendar - its experiment to crreate knowledges of nation. Making weather forecasts was very important for our ancestors. They couldnt listen to radio, read newspaper or watching TV, where we can get information about weather. Our ancestors observed nature and watched what was happen with her. Changes which were happen with nature affected their lifes, especially lifes of farmers. Farmers knew when are the best days for sowing cereals or when are the best days for crops.